Lessons for Diabetes Care from Kahlil Gibran's The Prophet - Kalra, Sanjay; Priya, Gagan; Ruder, Sundeep (Journal of Social Health and Diabetes, 2019)
Khalil Gibran's book The Prophet (1923) shares the conversations of a preacher, Almustafa, as he prepares to leave the city of Orphalese, where he spent 12 years. A collection of prose poetry fables continues to inspire people from all walks of life and remains as relevant as when it was written. This opinion piece uses curated verses from The Prophet to highlight the relevance of Gibran's timeless wisdom to modern diabetes care. It attempts to extract core lessons and present in a contemporary way for a modern health care professional to effect on and use.
Keywords: biopsychosocial model; patient-centered care; psychosocial aspects of diabetes